The The Influence of Family Ownership on Dividend Policy Moderated by Corporate Governance in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019 - Fitrilia Farida S; Muawanah, Umi; Setia, Kohar Adi (Politeknik Negeri Madiun, 2025)
This study examines the influence of family ownership on dividend policy, moderated by corporate governance practices. Family ownership, a dominant structure in Indonesian companies, prioritizes family welfare and often leads to agency conflicts, particularly Type II agency conflicts between majority family shareholders and minority shareholders. Using a sample of manufacturing companies listed on the Indonesia Stock Exchange, this research analyzes the relationship between family ownership and the dividend payout ratio while incorporating corporate governance mechanisms as a moderating variable. Corporate governance is proxied by board independence, institutional ownership, and board size to enhance transparency and reduce conflicts of interest.The findings reveal that family ownership has a positive but insignificant effect on dividend policy. However, corporate governance mechanisms significantly enhance dividend policy by balancing the interests of majority and minority shareholders, reducing moral hazard, and improving monitoring processes. This study contributes to understanding how governance structures mediate the relationship between ownership concentration and financial policy, providing valuable insights for stakeholders in developing effective governance frameworks.